A comparative cross-sectional study of HIV positive and HIV negative medical admissions at Helderberg Hospital, Western Cape, South Africa - Berrisford, Alison (Stellenbosch : Stellenbosch University, 2015)
Thesis (MB, ChB)--Stellenbosch University, 2016